The relationship between perceived organisational threat and compassion for others: Implications for the NHS. (23rd November 2017) - Henshall, Lauren Elizabeth; Alexander, Tim; Molyneux, Philip; Gardiner, Eric; McLellan, Ashleigh
Abstract : The National Health Service (NHS) is known to be a challenging place to work, with financial and performance targets placing increasing pressure on the organisation. This study aimed to investigate whether these pressures and threats might be detrimental to the quality of care and the compassion that the NHS strives to deliver. Quantitative data were collected via self‐report questionnaires from healthcare professionals across 3 NHS trusts in England in order to measure Self‐compassion; Compassion for Others; Perceived Organisational Threat; and Perceived Organisational Compassion. Qualitative data were also collected to explore the threats considered most pertinent to healthcare professionals at present. The key findings suggest that an increase in Perceived Organisational Threat may reduce an individual's ability to give compassion to others; however, Self‐compassion and Perceived Organisational Compassion were better predictors of Compassion for Others. This highlights the need to consider compassion at a systemic level, providing interventions and training not only to cultivate self‐compassion in healthcare professionals, but also to encourage compassion across the NHS more generally. In promoting self‐compassion and increasing the level of compassion that employees feel they receive at work, healthcare professionals may be better able to maintain or improve their level of compassion for service users and colleagues.